2018
DOI: 10.3390/plants7010017
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Study of the Potential Extracts from Selected Plants to Improve Surface Cleaning

Abstract: Environment hygiene is important for preventing infection and promoting a healthier environment in which to live or work. The goal of this study was to examine the antimicrobial effects of Citrus aurantifolia (key lime) juice and aqueous extracts of Cinnamomum iners (cinnamon) bark and Citrus hystrix (kaffir lime) leaves on the kinetic growth of Pseudomonas aeruginosa and methicillin resistance Staphylococcus aureus (MRSA). Antimicrobial activity was quantitatively evaluated using spectrophotometry and viable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 9 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Tree barks are widely used in traditional medicine to treat several diseases because of their medicinal properties grounded in the presence of phenolic compounds that can have antioxidant, antimicrobial, and anti-inflammatory activities [1,2,3]. The bark of Quercus species in particular is receiving increased attention because of its diverse traditional medicinal uses, its abundance and the low price of its wood residues, such as bark [4].…”
Section: Introductionmentioning
confidence: 99%
“…Tree barks are widely used in traditional medicine to treat several diseases because of their medicinal properties grounded in the presence of phenolic compounds that can have antioxidant, antimicrobial, and anti-inflammatory activities [1,2,3]. The bark of Quercus species in particular is receiving increased attention because of its diverse traditional medicinal uses, its abundance and the low price of its wood residues, such as bark [4].…”
Section: Introductionmentioning
confidence: 99%
“…The surface swabbed sample of the respective areas were diluted respectively in 10 ml sterile saline and then 1ml of each sample was pour plated into the nutrient agar plate in two replicates. The plates were then incubated at 37 °C for 24 hrs (Vong et al, 2018;. The number of colony forming unit per area sample=CFU/cm 2 was calculated using the formula (National Infection services, 2017).…”
Section: Preliminary Study Of Plant Extracts As a Disinfecting Agentmentioning
confidence: 99%
“…Floor surfaces are often covered by the dust containing of organic pollutants, fibres, particles, polycyclic aromatic compounds, minerals, metals, bacteria, pollen, allergens, etc. (Vong et al, 2018;APIC). Some of the clinically important bacteria found mainly in the indoor environment floors are Staphylococcus aureus, Bacillus sp., Pseudomonas aeruginosa, Escherichia coli, Salmonella sp., Klebsiella pneumonia, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-inflammatory, antibacterial, hepatoprotective, antidiabetic, gastroprotective, and antioxidant activity were assessed in previous reports (Moharram et al, 2015;Taib et al, 2020). It was reported that the biological effects of Quercus species were attributed to their high content of polyphenolic compounds which possess anti-inflammatory, antioxidant, and antidiarrheal activities (Salem et al, 2016;Dróżdż and Pyrzynska, 2018;Vong et al, 2018). The identified polyphenolic compounds in Quercus species were related to flavonoid, tannins and proanthocyanidins classes (Şöhretoğlu and Renda, 2020).…”
Section: Introductionmentioning
confidence: 97%